PROPERTIES OF ADHESIVE CHARACTERISTICS OF STRAINS PSEUDOMONAS AERUGINOSA - Port, E.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Adhesive properties strains Pseudomonas aeruginosa allocated in 2003-2004 from clinical sicks, and also museum strains and strains allocated from agricultural animals and birds were studied. The interrelation with resistance to antibiotics these strains were found. The tendency of growth adhesion properties is marked at increased resistance to antibiotics strains Pseudomonas aeruginosa.